A new formulation for quenching processes under restricted geometry conditions in the Slow Exchange Limit. (1st June 2014) - Sanchez, F.; Barrios, A.; Lopez-Lopez, M.; Lopez-Cornejo, P.; Bernal, E.; Sarrion, B.; Lebron, J.A.; Marchena, M.
A quantitative treatment of quenching processes under restricted geometry conditions in the Slow Exchange Limit is presented. The expressions for KSV have been obtained for this limit in some common situations that can arise in studies under restricted geometry conditions, such as an inhomogeneous quencher distribution in the solution, the presence of oxygen in solution, or the case of solutions containing a mixture of receptors. These situations have been considered and incorporated into the treatment.